Navigating Tradition and Modernity: The Impact of Transnational Islam in Gorontalo, Indonesia - Samsi Pomalingo; Kartini Kamaruzzaman; Idaman Idaman; Wirna Tangahu (Universitas Muhammadiyah Malang, 2024)
This research investigated the entry of Transnational Islam in Gorontalo, Indonesia, focusing on Tablighi Jamaat and Wahdah Islamiyah (Salafi). Addressing gaps in previous studies, this work explores why Gorontalo Muslims, despite early rejection, have embraced these movements. The study examines how transnational Islam responds to local cultural Gorontalo influences that affect the authenticity of Islamic teachings. Using a qualitative ethnographic approach, the research highlights key factors contributing to this acceptance, such as the emphasis on returning to the Quran and Sunnah, reinforcing aqidah (creed), tauhid (monotheism), and the importance of faith and good deeds. This study contributes to the growing body of literature on transnational Islam by offering new insights into its adaptation within local contexts, particularly in response to globalization. The findings are structured around key themes, such as doctrinal purity, dawah efforts, and the rejection of political agendas, which resonate with Gorontalo’s Muslim population across social classes. The theoretical frameworks of modernity and religious authority inform the analysis, illustrating how transnational movements negotiate global and local dynamics while maintaining a commitment to return to Islamic teachings under the guidance of the Al-Qur'an and the Sunnah of the Prophet.